Discrimination of Students in Specific Need: Cerebral Palsy - Wina Calista; Maratul Qiftiyah (Pedagogik Journal of Islamic Elementary School, 2020)
The purpose of this study was to describe acts of discrimination that occur between regular students and students with special needs in inclusive schools. This type of research is qualitative research with a case study approach. The subjects in this study were students with special needs in grade IV with the initials AN who had been diagnosed with cerebral palsy. The study was conducted at Giwangan Public Elementary School in Yogyakarta. Data collection techniques used in this study were interviews, observation, and documentation. The results showed that the forms of discrimination between regular students and students with special needs with cerebral palsy disorders in inclusive schools were ridicule, rejection, and physical contact. As a result, students with special needs withdraw from the social environment at school. Inclusive schools as child-friendly schools can certainly eliminate discriminatory attitudes in schools. The existence of acts of discrimination that still occur in inclusive schools means that schools have not been able to accommodate all students.